Energy Efficiency Analysis Using Pinch Technology in the Preliminary Design of a Nitromethane Plant from Nitric Acid and Methane - Yasmin Safitri; Zahra Aulia Putri; Desinta Rahma Prajaningrum; Abellia Puteri Hapsari (Vocational College of Universitas Diponegoro, 2025)
The production process of nitromethane through vapor phase nitration reaction between nitric acid and methane is a highly energy-intensive process requiring heating at high temperatures up to 653 K. The significant dependence on external utilities results in high operational costs and carbon emissions, necessitating energy system optimization to enhance efficiency and product competitiveness. This study aims to analyze energy efficiency in the preliminary design of a 25,000 tons per year nitromethane plant using pinch technology to determine minimum energy requirements and design an optimal Heat Exchanger Network. The pinch analysis method was applied by extracting process stream data including mass flow rate, heat capacity, inlet and outlet temperatures from four main heat exchanger units. The analysis was conducted using problem table, composite curve, and grid diagram with a ΔTmin value of 10 K. The analysis results show that the system requires a minimum hot utility of 798.418 kW and cold utility of 1,925.67 kW with a pinch temperature at 308 K. The optimal Heat Exchanger Network configuration successfully reduced the furnace load to 313.303 kW through internal heat integration, utilizing sensible heat from high-temperature reactor products for feed preheating. The implementation of pinch technology in this system has the potential to generate significant energy savings compared to conventional design, while contributing to CO₂ emission reduction and enhancing sustainability of chemical industrial processes.